Bioactive compounds from blueberry and blackcurrant powder alter the physicochemical and hypoglycaemic properties of oat bran paste. (May 2021) - Hui, Xiaodan; Wu, Gang; Han, Duo; Gong, Xi; Stipkovits, Letitia; Wu, Xiyang; Tang, Shuze; Brennan, Margaret A.; Brennan, Charles S.
Abstract: Cereal foods supplemented with fruit ingredients have attracted the attention of consumers due to their bioactive compounds which confer health promoting effects. In this study, oat bran was mixed with 0%, 10%, 15% and 25% (w/w) of blueberry or blackcurrant powder, to form blueberry and blackcurrant enriched oat bran pastes. Pasting properties, colour profiles, and nutritional compositions of these pastes were evaluated. The bioactive compounds in the extracts of pastes were identified. An in vitro digestion procedure was employed to observe the effects of bioactive compounds on predicted glycaemic response of pastes. Delphinidin, cyanidin, petunidin, and malvidin were identified in extracts of 25% blueberry and blackcurrant powder-enriched pastes. Results showed that enrichment with blueberry or blackcurrant powder significantly altered the pasting viscosities and the colour profiles, and increased the content of phenolic compounds (in particular the phenolic acids and the anthocyanins) of pastes ( p < 0.05 ), whilst decreasing the extent of starch degradation and the reducing sugar released from oat bran paste during the in vitro digestion ( p < 0.05 ). Our findings suggested that enrichment with blueberry or blackcurrant powder into oat bran provided healthier food characteristics, and manipulated the hypoglycaemic property of pastes. Highlights: Pasting properties of oat bran was reduced with blueberry and blackcurrant addition. Starch digestion decreased with blueberry or blackcurrant addition. Total anthocyanin levels increased with blueberry and blackcurrant addition. HPLC confirmed the presence of phenolic acids in the enhanced pastes.